1990
DOI: 10.1099/00221287-136-8-1645
|View full text |Cite
|
Sign up to set email alerts
|

Crinalium epipsammum sp. nov.: a filamentous cyanobacterium with trichomes composed of elliptical cells and containing poly- -(1,4) glucar (cellulose)

Abstract: This paper describes the isolation and characterization of a new species of cyanobacterium, Crinalium epipSammum. The assignment to the genus Crinalium, first described by Crow (1927), is based on a property which is u n d for cyanobacteria: trichomes viewed in cross-section are elliptical rather than circular. This organism was isolated from the surface layer of sandy soil of coastal dunes in The Netherlands. The organism is non-motile and drought resistant, and its cell surface is hydrophilic. The temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 25 publications
1
24
0
1
Order By: Relevance
“…Also, the DNA of this organism has an exceptionally low GC content and these characteristics may reflect its low-nitrogen habitat and its incapability of fixing nitrogen. The cellulose detected in C. epipsammum might be present in non-crystalline form (de Winder et al, 1990); the presence of cellulose with low crystallization has also been reported for other cyanobacterial strains (Nobles, Romanovicz, and Brown, 2001). In native form neither cellulose I nor II was detected in C. epipsammum but in its extracted form cellulose II was found, probably as the result of the alkali treatment.…”
Section: Cellulose Structure and Physiological Functionsupporting
confidence: 54%
See 2 more Smart Citations
“…Also, the DNA of this organism has an exceptionally low GC content and these characteristics may reflect its low-nitrogen habitat and its incapability of fixing nitrogen. The cellulose detected in C. epipsammum might be present in non-crystalline form (de Winder et al, 1990); the presence of cellulose with low crystallization has also been reported for other cyanobacterial strains (Nobles, Romanovicz, and Brown, 2001). In native form neither cellulose I nor II was detected in C. epipsammum but in its extracted form cellulose II was found, probably as the result of the alkali treatment.…”
Section: Cellulose Structure and Physiological Functionsupporting
confidence: 54%
“…Although it has been known for a long time that cyanobacteria can produce cellulose (de Winder et al, 1990;Nobles, Romanovicz, and Brown, 2001), the mechanism and regulation of the process have never been investigated. The literature on cellulose production in cyanobacteria reports production of non-or semi-crystalline cellulose (de Winder et al, 1990;Nobles, Romanovicz, and Brown, 2001). A reason for the semi-crystalline nature of the cellulose may be the complex mixed-polysaccharide cell-wall layers produced by cyanobacteria.…”
Section: Macromolecular Solar Biofuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanobacteria are often found in warm, low nutrient environments (De Winder et al 1990), and are typically more thermotolerant than eukaryotic algae (Barsanti and Gualtieri, 2006). Members of the single-celled cyanobacterial genus Thermosynechococcus are capable of surviving at 73-74°C, whilst thermophillic filamentous cyanobacteria typically occupy a lower temperature range of 55-62°C (Seckbach, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…glycogen and poly-alkanoate formation. Significantly, homologous expression enzymes that catalyze the formation of extracellular cellulose has also been observed in natural isolates of cyanobacteria, like in the filamentous Crinalium epipsammum (Dewinder et al, 1990).…”
Section: Current Biofuel Production Strategiesmentioning
confidence: 94%